DISTRIBUTION CHARACTERISTICS OF CHICKEN ECTOPARASITES (Ustozlar uchun, 2024)
Abstract. This article presents literature data and results of preliminary research about ectoparasites that are widespread and cause great economic damage in chicken coops and some poultry farms. Their biology, distribution, clinical signs, epizootology and preventive measures are presented.